2016
DOI: 10.1111/nph.14098
|View full text |Cite
|
Sign up to set email alerts
|

Plant hydraulics improves and topography mediates prediction of aspen mortality in southwestern USA

Abstract: SummaryElevated forest mortality has been attributed to climate change-induced droughts, but prediction of spatial mortality patterns remains challenging. We evaluated whether introducing plant hydraulics and topographic convergence-induced soil moisture variation to land surface models (LSM) can help explain spatial patterns of mortality.A scheme predicting plant hydraulic safety loss from soil moisture was developed using field measurements and a plant physiology-hydraulics model, TREES. The scheme was upsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 98 publications
4
89
0
1
Order By: Relevance
“…Plant functional traits are typically well correlated with the physical environment and are important in determining plant performance under environmental stress (Soudzilovskaia et al, ). Drought‐induced hydraulic dysfunction may strongly limit the distribution of species along environmental gradients of water availability (Choat, Sack, & Holbrook, ; Kursar et al, ; Larter et al, ; Pockman & Sperry, ), define critical drought tolerance thresholds (Brodribb & Cochard, ; Urli et al, ), and be used to predict drought‐induced tree mortality (Tai, Mackay, Anderegg, Sperry, & Brooks, ; Xu, Medvigy, Powers, Becknell, & Guan, ). However, determining species overall drought susceptibility will depend on a more thorough understanding of the suite of traits that define plant water use and drought response strategies (Blackman, Aspinwall, Resco de Dios, Smith, & Tissue, ; Brodribb, McAdam, & Carins Murphy, ; Gleason, Blackman, Cook, Laws, & Westoby, ) and their relationship to traits regulating growth and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Plant functional traits are typically well correlated with the physical environment and are important in determining plant performance under environmental stress (Soudzilovskaia et al, ). Drought‐induced hydraulic dysfunction may strongly limit the distribution of species along environmental gradients of water availability (Choat, Sack, & Holbrook, ; Kursar et al, ; Larter et al, ; Pockman & Sperry, ), define critical drought tolerance thresholds (Brodribb & Cochard, ; Urli et al, ), and be used to predict drought‐induced tree mortality (Tai, Mackay, Anderegg, Sperry, & Brooks, ; Xu, Medvigy, Powers, Becknell, & Guan, ). However, determining species overall drought susceptibility will depend on a more thorough understanding of the suite of traits that define plant water use and drought response strategies (Blackman, Aspinwall, Resco de Dios, Smith, & Tissue, ; Brodribb, McAdam, & Carins Murphy, ; Gleason, Blackman, Cook, Laws, & Westoby, ) and their relationship to traits regulating growth and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Tai et al . () also found that including topography to approximate lateral redistribution improved predictions of Aspen, Populus tremuloides , mortality in Colorado. Our approach expands upon Tai et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our approach expands upon Tai et al . (), by providing an alternative framework that cohesively integrates plant physiological thresholds limiting hydraulic capacity (Fig. b) and landscape processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations